Acoustic cavitation and bubble dynamics - LAUTERBORN, Werner; KURZ, Thomas; METTIN, Robert; KOCH, Philipp; KROENINGER, Dennis; SCHANZ, Daniel (Archives of Acoustics, 2008)
Acoustic cavitation is investigated experimentally and theoretically starting with a single bubble in an acoustic field. The single bubble is trapped in an acoustic resonator and observed by high-speed imaging and acoustic measurements following its transient dynamics to a possible steady state after generation by laser light. Numerical calculations are done to explore the regions of survival for acoustically driven bubbles with respect to dissolution or growth, surface oscillations and positional stability in a standing sound field. The interior gas dynamics is explored via molecular dynamics simulations. A glance is thrown at the complex dynamics of multi-bubble systems.